The Response of Variant Histology Bladder Cancer to Intravesical Immunotherapy Compared to Conventional Cancer - Gofrit, Ofer N.; Yutkin, Vladimir; Shapiro, Amos; Pizov, Galina; Zorn, Kevin C.; Hidas, Guy; Gielchinsky, Ilan; Duvdevani, Mordechai; Landau, Ezekiel H.; Pode, Dov (Frontiers in Oncology, 2016)
Background: High-grade urothelial carcinomas (UC) often show foci of variant differentiation. There is limited information in the literature about the response of these variant urothelial tumors to immunotherapy with Bacillus Calmette Guerin (BCG). We compared the response to treatment with BCG of UC containing glandular, squamous, nested and micropapillary types of differentiation to response of conventional non-muscle invasive high-grade urothelial carcinoma. Methods: A total of 100 patients were diagnosed with variant histology urothelial cancer between June 1995 and December 2013. 41 patients with Ta or T1, confirmed by 2nd look biopsies, received immunotherapy with BCG. Fourteen patients in this group were diagnosed with micropapillary differentiation 13 patients with squamous differentiation, in 9 patients glandular differentiation was seen and in 7 patients nested variant. The control group included 140 patients with conventional high-grade UC. Both groups have been treated and followed similarly. Findings: Patients with variant tumors had similar clinical features to patients with conventional disease including: age, males to female ratio, stage, presence of Tis and median follow-up. Patients with variant tumors had a significantly worse prognosis compared to patients with conventional high-grade UC including: 5-year recurrence-free survival (63.5% Vs. 71.5%, p=0.05), 5-year progression to≥T2 -free survival (60% Vs. 82.5%, p=0.002), 5-year disease-specific survival (73% Vs. 92.5%, p=0.0004) and overall survival (66% Vs. 89.5%, 0.05). Interpretation: A patient with variant bladder cancer treated with intra-vesical immunotherapy has a 27% chance of dying from this disease within 5-years compared to 7.5% for a patient with conventional high-grade UC.